Characterization and optimization of oil microcapsules from Attalea phalerata Mart. for the preservation of bioactive compounds - Fernando Freitas de Lima; Caroline Honaiser Lescano; Elaine Florinda Rodrigues de Oliveira; Farayde Matta Fakhouri; Izabel Cristina Freitas Moraes; Cândida Aparecida Leite Kassuya; Eliana Janet Sanjinez-Argandoña (Universidade de São Paulo, 2019)
This study aimed microencapsulating Attalea phalerata Mart. oil, containing high carotenoid and phenolic compounds content, with Arabic gum and gelatin, using the complex coacervation method. The yield, efficiency, morphology of microcapsules and content of phenolic compounds, carotenoids and antioxidant activity in different processes conditions (concentration of the filling, temperature and agitation speed) were evaluated. The results showed 88% of yield, efficiency up to 70% and a characteristic size of microcapsules. The amount of carotenoids was high in crude oil (394.84 µg of carotenoids/g oil) and the microencapsulation tests showed amounts of 19.19 to 166.40 µg of carotenoids/g oil. The phenolic compounds in the crude oil were 20.73 mg GAE/g sample and the microencapsulation tests showed amounts of 3.17 to 15.16 mg GAE/g oil. The values of bioactive compounds influenced in the antioxidant activity though ABTS•+ method with values of 161.70 µM trolox/g oil to crude oil and 7.70 and 159.54 µM trolox/g oil for microcapsules tests.